High syphilis seropositivity in European brown hares (Lepus europaeus), Lower Saxony, Germany - Hisgen, Linda; Abel, Lena; Hallmaier-Wacker, Luisa K; Lueert, Simone; Siebert, Ursula; Faehndrich, Marcus; Strauss, Egbert; Voigt, Ulrich; Nováková, Markéta; Šmajs, David; Knauf, Sascha (Transboundary and emerging diseases, 2020)
The lagomorph-infecting Treponema paraluisleporidarum is a close relative of the human syphilis-bacterium Treponema pallidum. There is a paucity of information on the epidemiology of hare syphilis and its relationship to the rabbit- and human-infecting treponemes that cause syphilis. In our study, we tested 734 serum samples from European brown hares (Lepus europaeus) collected between 2007 and 2019 in the federal state of Lower Saxony, Germany, for the presence of antibodies against T. paraluisleporidarum. Since T. paraluisleporidarum cross-reacts with T. pallidum antigen, we used a commercially available T. pallidum-particle agglutination (TP-PA) assay to test for the presence of antibodies. A high seropositivity (n = 405/734) was detected. An additional 233 serum samples were retested using a fluorescent treponemal antibody absorption test to confirm the results of the TP-PA assay. Our results show that infection is widespread in Lower Saxony and suggest a horizontal (sexual) transmission mode since adult hares show significantly higher seropositivity than subadults (odds ratio: 0.03 [95% CI 0.02-0.05], p < .0001). No difference was detected based on gender (odds ratio: 0.79 [95% Cl 0.58-1.07], p = .1283). Further studies are warranted to genetically characterize the T. paraluisleporidarum strains that infect wild hares.
Keywords: serology; rabbit; Lepus europaeus; spirochaete; Treponema paraluisleporidarum; lagomorpha